ETIKA SEORANG GURU DALAM PROSES BELAJAR MENGAJAR - Azhara, Sabrina; Ginting, Rahmadani Fitri (Cahaya Ilmu Bangsa Institute, 2024)
The ethics of a teacher in the teaching and learning process plays a crucial role in creating a positive and productive educational environment. Teachers are figures who hold a respectable and noble position, as expressed by al-Ghazali: